2010
DOI: 10.3758/s13421-010-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of judgment-of-learning resolution to past test performance, new learning, and forgetting

Abstract: When people judge their learning of items across study-test trials, their accuracy in discriminating between learned and unlearned items improves on the second trial. We examined the source of this improvement by estimating the contribution of three factors-memory for past test performance (MPT), new learning, and forgetting-to accuracy on trial 2. In Experiment 1, during an initial trial, participants studied paired associates, made a judgment of learning (JOL) for each one, and were tested. During the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 26 publications
7
39
0
Order By: Relevance
“…In addition, past-test correlations exceeded the Phase 2 relative-accuracy correlations. These results concur with past results and conclusions (i.e., Ariel & Dunlosky, 2011;Finn & Metcalfe, 2007, 2008cf. King, Zechmeister, & Shaughnessy, 1980), and they further suggest that past-test information is a major contributor to increases in relative accuracy across phases.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In addition, past-test correlations exceeded the Phase 2 relative-accuracy correlations. These results concur with past results and conclusions (i.e., Ariel & Dunlosky, 2011;Finn & Metcalfe, 2007, 2008cf. King, Zechmeister, & Shaughnessy, 1980), and they further suggest that past-test information is a major contributor to increases in relative accuracy across phases.…”
Section: Discussionsupporting
confidence: 94%
“…Although items that participants had recalled on Phase 1 received further adjustment from this anchor on Phase 2, the adjustment was insufficient to produce accuracy, and these items exhibited considerable underconfidence. In addition, the Experiment 1 results also demonstrated that past-test information is likely responsible for increases in the relative accuracy of JOLs across study-test phases (see also Ariel & Dunlosky, 2011;Finn & Metcalfe, 2007, 2008.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Items recalled during the trial 1 test were given a high JOL during Trial 2 and items that were not recalled were given a low JOL during Trial 2. Accordingly, Metcalfe (2007, 2008) suggested that participants rely on Memory for Past Test (MPT), judging future memorability based on whether information was recalled during a previous test (see also Serra & Ariel, 2014; for other influences, see Ariel & Dunlosky 2011;Tauber & Rhodes, 2012).…”
Section: Predicting Future Test Performancementioning
confidence: 99%
“…Castel suggested that by soliciting pre-JOLs, participants were able to focus on extrinsic factors that are important for actual memory performance (e.g., serial position of an item). When these extrinsic factors are made salient, participants are able to incorporate relevant information into their memory predictions (see also Ariel & Dunlosky, 2011).…”
Section: Test Performancementioning
confidence: 99%